ANALISIS FAKTOR YANG MEMPENGARUHI STABILITAS PERBANKAN SYARIAH DAN KONVENSIONAL DI INDONESIA PERIODE 2008-2022 - Rizma Novita Sari; Farah Wulandari Pangestuty (Islamic Economics and finance in Focus, 2024)
This study aims to analyze the effects of Liquidity Risk, Credit Risk, Control of Corruption, Inflation, and Economic Growth on the stability of Islamic and Conventional banks in Indonesia. The population in this study consists of Islamic and Conventional banks registered with the OJK during the period 2008-2022. The sampling technique employed is purposive sampling, resulting in a total sample of 11 banking companies. The data used in this study are secondary data obtained from the financial statements of each bank. Bank stability is measured using the Z-score proxy. The study utilizes panel data regression with a Fixed Effect Model.The research findings indicate that Liquidity Risk, measured by the F/LDR ratio, has a negative impact on Shariah banks, while it does not affect conventional banks. Control of Corruption has a positive impact on the stability of both Shariah and conventional banks. Economic growth does not have a significant impact on either type of bank, whether Shariah or conventional. Inflation does not influence the stability of either Shariah or conventional banks.